Field soil properties and experimental nutrient additions drive the nitrous oxide ratio in laboratory denitrification experiments: a systematic review - Foltz, Mary E.; Alesso, Agustín; Zilles, Julie L. (Frontiers in Soil Science, 2023)
Nitrous oxide (N2O), which contributes to global climate change and stratospheric ozone destruction, can be produced during denitrification. Although the N2O ratio, a measure of denitrification completion, is influenced by various properties, studies have largely been limited to site-or treatment-specific conclusions. The primary objective of this study was to identify important factors driving N2O ratios and their relationships in soils by systematically reviewing and quantitatively evaluating results from published laboratory denitrification studies. A database with 60 studies (657 observations) was compiled, including studies meeting the minimum criteria: (i) laboratory experiments on soils, (ii) nutrient (carbon and/or nitrogen) addition, and (iii) N2O and dinitrogen gas measurements. Of these, 14 studies (100 observations) had sufficient data for inclusion in the metaanalysis to assess the effect of added nutrients on the N2O ratio. Furthermore, we modeled the effect of moderators on treatment effect by fitting a meta-regression model with both quantitative and categorical variables. Close review of studies in the database identified soil pH, carbon addition, and nitrogen addition as important variables for the N2O ratio, but trends varied across studies. Correlation analysis of all studies clarified that soil pH was significantly correlated with the N2O ratio, where soils with higher pH had lower N2O ratios. The meta-analysis further revealed that nutrient addition had an overall significant, positive treatment effect (0.30 ± 0.03, P<.0001), indicating that experimentally adding nutrients increased the N2O ratio. The model was most significantly improved when soil texture was used as a moderator. The significance of soil texture for the N2O ratio was a major finding of this study, especially since the assays were usually conducted with soil slurries. Overall, this study highlights the importance of field soil properties (i.e., pH, texture) and laboratory conditions (i.e., nutrient addition) in driving the N2O ratio and N2O production from denitrification in soils.